(untitled) (European journal of volunteering and community-based projects, 2021)
The Moringa oleifera also called “Drumstick tree”, to its various pharmacological uses and nutritional adaptability worth is comprehensively all over the earth. The tree parts; stem, bark, gum, roots, and mostly leaves are great provenance of vitamins, minerals, and numerous clinically beneficial secondary-metabolites and also a significant role in diabetic-resistance. The virtual-study may exist significant in terms of expanding the number of successful antidotes derived through this herb and plan to obtain the potent-phytochemicals amalgam of miracle tree even an agent for the curative potential opponent the Diabetes-Mellitus (DM) by computational screening. The structure of the top three selected phytochemicals was extracted from previous works of literature, Drug Bank database, PubChem-database, and screened with mutated protein from PDB structure (Crystal structure of insulin receptor kinase domain in complex with cis-(R)-7-(3-(azetidin-1-ylmethyl) cyclobutyl)-5-(3-((tetrahydro-2H-pyran-2-yl)methoxy)phenyl)-7H-pyrrolo[2,3-d]pyrimidin-4-amine) through PyRx-docking tool. After, these three potent compounds: Anthraquinone, Serpentine, and Laurifolin were obtained, which showed successful binding within the targeted protein’s active binding pocket; Anthraquinone-chain A: ASP-1177 aa (amino acid-complex) site, Laurifolin-Chain A: ASP-1110 aa, and Serpentine-Chain A: MET-1103 aa. The main features of the pharmacophore model based on ligands were revealed showed i.e. through molinspiration, swiss adme, admetSAR and exhibited acceptable drug-like properties; HBA (4,2,2), HBD (0,2,0), with the potent surface-binding active site: position A: 1159 by CASTp and structural visualized through Chimera Tool, and the protein functional network analysis of INSR Gene-associated with other via INSRR, IRS1, IRS2, SHC1, IGF1, PTPN1, INS, PTPN2, IGF1R, GRB14 of targeted plant Moringa oleifera against DM through STRING Database and gene-regulate expression were analyzed. Our finding proposes that docking potent these phytochemicals and gene functionality in M.oleifera may be utilized as a pharmaceutical candidate for diabetes and further investigate in future research.